Pengaruh Model Guided Discovery Learning Terhadap Hasil Belajar Matematika Pecahan Siswa Kelas III SDN 20 Tala-Tala Kecamatan Bissappu Kabupaten Bantaeng - Indah Ayu Lestari; Andi Husniati; Ahmad Syamsuadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of Guided Discovery Learning on the learning outcomes of students in fractions of Class III SDN 20 Tala-Tala, Bissappu District, Bantaeng Regency. The type of research used in this study is experimental research, especially Pre-experimental. The sample in this study was 25 students. Data collection techniques were carried out using learning outcome tests and observation sheets. Data analysis techniques in this study were descriptive data analysis techniques and inferential data analysis techniques. The results of the study showed that there was an effect of the Guided Discovery Learning model on the mathematics learning outcomes of class III students of SDN 20 Tala-Tala, Bissappu District, Bantaeng Regency, as shown by the results of the t-test analysis showing that the significance value obtained (Sig = 0.001) was smaller than the specified alpha value of 0.05 (0.001 <0.05), then H0 was rejected and H1 was accepted, meaning that there was an effect of the Guided Discovery Learning model on the mathematics learning outcomes of class III students of SDN 20 Tala-Tala, Bissappu District, Bantaeng Regency. In addition, the results of learning mathematics before the implementation of the Guided Discovery Learning model in the pretest with an average value of 60, there was an increase in the posttest with an average value of 80.4. Based on the results obtained, it can be concluded that there is an influence of the Guided Discovery Learning model on the mathematics learning outcomes of class III students of SDN 20 Tala-Tala, Bissappu District, Bantaeng Regency. Keywords: Guided Discovery Learning Model, Learning Outcomes, Mathematics